Carnitine and physical exercise - Heinonen, O. J. (Sports Medicine, 1996)
Carnitine plays a central role in fatty acid (FA) metabolism. It transports long-chain fatty acids into mitochondria for beta-oxidation. Carnitine also modulates the metabolism of coenzyme-A (CoA). It is not surprising that the use of supplementary carnitine to improve physical performance has become widespread in recent years, although there is no unequivocal support to this practice. However, critical reflections and current scientific-based knowledge are important because the implications of reduced or increased carnitine concentrations in vivo are not thoroughly understood. Several rationales have been forwarded in support of the potential ergogenic effects of oral carnitine supplementation. However, the following arguments derived from established scientific observations may be forwarded: (i) carnitine supplementation neither enhances FA oxidation in vivo or spares glycogen or postpones fatigue during exercise. Carnitine supplementation does not unequivocally improve performance of athletes; (ii) carnitine supplementation does not reduce body fat or help to lose weight; (iii) in vivo pyruvate dehydrogenase complex (PDC) is fully active already after a few seconds of intense exercise. Carnitine supplementation induces no further activation of PDC in vivo; (iv) despite an increased acetyl-CoA/free CoA ratio, PDC is not depressed during exercise in vivo and therefore supplementary carnitine has no effect on lactate accumulation; (v) carnitine supplementation per se does not affect the maximal oxygen uptake (VO2max); (vi) during exercise there is a redistribution of free carnitine and acylcarnitines in the muscle but there is no loss of total carnitine. Athletes are not at risk for carnitine deficiency and do not have an increased need for carnitine. Although there are some theoretical points favouring potential ergogenic effects of carnitine supplementation, there is currently no scientific basis for healthy individuals or athletes to use carnitine supplementation to improve exercise performance.